Social Media Analysis on Interest in Buying Imported Used Shoes at SOM Sneakers - Amanda, Essi Laura; Saskia, Ainun; Fajri, M Yudi; Simanungkalit, Jessica Br; Meiriza, Mica Siar (CV. Rayyan Dwi Bharata, 2025)
This study investigates the impact of social media on consumer interest in purchasing imported secondhand footwear, focusing on SOM Sneakers as a case study. Employing a mixed-methods approach combining surveys and interviews, the research demonstrates a significant influence of social media on consumer buying decisions. This influence is mediated through increased brand awareness, influencer marketing, consumer reviews, and direct brand-consumer interaction, particularly on platforms like Instagram and TikTok, fostering engagement, building trust, and ultimately driving purchase intent. The findings offer valuable insights for both academic discourse and the development of effective marketing strategies within the secondhand footwear industry.